2021
DOI: 10.21518/2079-701x-2021-5-12-20
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of functional dyspepsia and irritable bowel syndrome by revised Rome IV criteria: meta-analysis

Abstract: Introduction. Functional dyspepsia (FD) and irritable bowel syndrome (IBS) overlap is an adverse clinical situation, as patients with this syndrome have more severe clinical manifestations resulting in significant reductions in quality of life. For now, there are no meta-analytical papers that would summarize the frequency of FD – IBS overlap using the revised Rome IV criteria. Objective. To organize data on the prevalence of FD – IBS overlap using the revised Rome IV criteria.Materials and methods. A search f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…The practical situation becomes even more complicated when overlapping symptoms. It should be noted that publications note significant differences in the reported incidence of intersection syndromes in DGBI and virtually no evaluation of the drug treatment efficacy and safety for such conditions [22,23]. It has also been shown that the natural history in people with IBS overlapping FD is more severe than in those with isolated IBS [24].…”
Section: Discussionmentioning
confidence: 99%
“…The practical situation becomes even more complicated when overlapping symptoms. It should be noted that publications note significant differences in the reported incidence of intersection syndromes in DGBI and virtually no evaluation of the drug treatment efficacy and safety for such conditions [22,23]. It has also been shown that the natural history in people with IBS overlapping FD is more severe than in those with isolated IBS [24].…”
Section: Discussionmentioning
confidence: 99%
“…Следует обратить внимание на то, что в публикациях отмечаются значительные различия приводимых данных о частоте синдромов перекреста при DGBI и практически отсутствуют работы по оценке эффективности и безопасности медикаментозного лечения таких состояний [22,23]. Также показано, что естественное течение болезни у людей с СРК, перекрывающимся ФД, более тяжелое, чем у людей с изолированным СРК [24].…”
Section: таблица 7 результаты описательной статистики гематологически...unclassified